A survey of approaches combining safety and security for industrial control systems. (July 2015) - Kriaa, Siwar; Pietre-Cambacedes, Ludovic; Bouissou, Marc; Halgand, Yoran
Abstract: The migration towards digital control systems creates new security threats that can endanger the safety of industrial infrastructures. Addressing the convergence of safety and security concerns in this context, we provide a comprehensive survey of existing approaches to industrial facility design and risk assessment that consider both safety and security. We also provide a comparative analysis of the different approaches identified in the literature. Highlights: We raise awareness of safety and security convergence in numerical control systems. We highlight safety and security interdependencies for modern industrial systems. We give a survey of approaches combining safety and security engineering. We discuss the potential of the approaches to model safety and security interactions.